Measuring the colombian “success” story - Feldmann, Andreas (Revista de Ciencia Política, 2019)
This article discusses the evolution of state capacity in Colombia. Drawing on the general debate regarding the conceptualization and measurement of the state, the piece tracks the record of the Colombian state in the last decade. The article posits that, contrary to the conventional wisdom, the strength of the Colombian state has increased only marginally in the last 10 years. This improvement derives from important gains in two of Michael Mann’s (1986) infrastructural power dimensions –territorial reach and bureaucratic capacity. Lack of substantial improvements in Mann’s third infrastructural dimension– autonomy vis-à-vis non-states actors– and setbacks in the state legitimacy dimension make the gains in state capacity modest rather than robust.